2018
DOI: 10.1002/mc.22903
|View full text |Cite
|
Sign up to set email alerts
|

S100A11 promotes cell proliferation via P38/MAPK signaling pathway in intrahepatic cholangiocarcinoma

Abstract: S100A11 is reported to associate with progression and poor prognosis in several tumors. We previously reported that S100A11 was highly expressed in intrahepatic cholangiocarcinoma (ICC) cells and promoted TGF-β1-induced EMT through SMAD2/3 signaling pathway. Here, we explored the prognostic role of S100A11 on ICC patients and preliminary molecular mechanisms how S100A11 regulated ICC cell proliferation. Our results showed that S100A11 was obviously increased in ICC tumor tissues. High expression of S100A11 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…As the heatmap shows, the key genes related to the MAPK signaling pathway were significantly upregulated, while FoxA2 expression was significantly decreased in FoxA2 -/- mice. As previous reports showed, the MAPK signaling pathway extensively participates in cell proliferation and differentiation and is related to tumor prognosis including in intrahepatic cholangiocarcinoma [2830]. Consistently, the results of the IHC analysis suggested that the expression of key mediators in the MAPK signaling pathway, such as p-ERK1/2 and RAS, was significantly increased.…”
Section: Discussionsupporting
confidence: 80%
“…As the heatmap shows, the key genes related to the MAPK signaling pathway were significantly upregulated, while FoxA2 expression was significantly decreased in FoxA2 -/- mice. As previous reports showed, the MAPK signaling pathway extensively participates in cell proliferation and differentiation and is related to tumor prognosis including in intrahepatic cholangiocarcinoma [2830]. Consistently, the results of the IHC analysis suggested that the expression of key mediators in the MAPK signaling pathway, such as p-ERK1/2 and RAS, was significantly increased.…”
Section: Discussionsupporting
confidence: 80%
“…The return to normal values of S10AB under treatment is also consistent with our previous finding of a dramatic increase in this protein’s abundance specifically observed in neoplastic vs. preneoplastic rat mesothelial cells [ 15 ]. The comparable S10AB values observed in curcumin-treated and normal rats lead to the conclusion that the activation of different signaling pathways, which were associated with S10AB increases in different types of cancer [ 38 , 39 , 40 , 41 ], was cancelled under treatment. Finally, we found the same opposite evolution of S10A4 and S10A8 as that observed in oral squamous cell carcinomas, suggesting that combinatorial analysis of these two S100 proteins would predict the lesions’ degree of malignancy [ 42 ].…”
Section: Discussionmentioning
confidence: 86%
“…For example, Wang et al, clari ed that TSPAN1 was involved in CCA progression via PI3K/AKT pathway [41]. Zhang et al, suggested that S100A11 promoted cell proliferation by p38/MAPK signaling pathway in iCCA [42]. This study discovered that GSG2 knockdown contributed to downregulation of P-Akt, CCND1, PIK3CA, and upregulation of MAPK9.…”
Section: Discussionmentioning
confidence: 76%